3-Dimensional Plating System in the Management of Mandibular Parasymphysis Fracture: A Case Report - Harsh Mohan Pathak1 , Satyabrata Pattnaik1 , Wasim Alam2 , Sanchari Sinha Roy2 , Soumyakanti Roy3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The aim of treating mandibular fracture is to recover the anatomic structure and functionwith special caution in restoring the occlusion. Champy’s miniplate fixation has been the most commonlyusedprocedure amongst the various treatment modalities available. The 3-dimensional (3D) plating is fairlynew for treating mandibular fractures.Aim: This research was performed to equate the effectiveness, flexibility, and rigidity of 3-dimensionalplates with that of 2 mm titanium miniplates in anterior mandibular fracture surgical management.Material and Method: The study was conducted on a singlepatient with anterior mandibular fracture (Rightparasymphysisregion).The patient’s preoperative, intraoperative, and postoperative clinical and radiological findings were recordedin a proforma.Results: The timerequired to adapt and fix the miniplates were slightly more than3-D plates and results weresignificant. Skeletaland occlusal stability was maintained.Conclusion: the 3-dimensional plate is as effective as conventional miniplates in the treatment of anteriormandibular fractures. Its the ease of use and reduced working hours that are advantages over traditionalminiplates.